Testing Willingness to Pay Elicitation Mechanisms in the Field: Evidence from Uganda - Konrad B. Burchardi; Jonathan de Quidt; Selim Gulesci; Benedetta Lerva; Stefano Tripodi (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Researchers frequently use variants of the Becker-DeGroot-Marschak (BDM) mechanism to elicit willingness to pay (WTP). These variants involve numerous incentive-irrelevant design choices, some of which carry advantages for implementation but may deteriorate participant comprehension or trust in the mechanism, which are well-known problems with the BDM. We highlight three such features and test them in the field in rural Uganda, a relevant population for many recent applications. Comprehension is very high, and 86 percent of participants bid optimally for an induced-value voucher, with little variation across treatments. This gives confidence for similar applications, and suggests the comprehension-expediency trade-off is mild.
Keywords: C90; C93; D44; O12; 330; willingness to pay; Becker-DeGroot-Marschak; field experiment